2021
DOI: 10.1097/bot.0000000000001856
|View full text |Cite
|
Sign up to set email alerts
|

Risk of Injury to the Neurovascular Structures in the Pararectus Approach Used in Acetabular Fractures: A Cadaver Study

Abstract: Objectives: Complex acetabular fractures involving the quadrilateral plate may necessitate infrapectineal buttress plating, which can be performed through the pararectus approach. The aim of this cadaveric study was to identify the anatomical guide points to protect neurovascular structures at the risk of injury during the pararectus approach. Methods: Six fresh frozen cadavers (12 hemipelves) were dissected in this study. Location of the inferior epiga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…When encountered in anterior pelvic approaches, it is associated with significant bleeding events [2][3][4][5][6]. Anatomical studies have observed a prevalence ranging from 33% to 83% [8][9][10][11][12][13]. Clinical series report a lower prevalence of 1-52% [3,10,14], and radiographic studies indicate a prevalence of 14-33% (arterial CM) and 29-51% (venous CM) [19][20][21] (Tables 4, 5, and 6).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…When encountered in anterior pelvic approaches, it is associated with significant bleeding events [2][3][4][5][6]. Anatomical studies have observed a prevalence ranging from 33% to 83% [8][9][10][11][12][13]. Clinical series report a lower prevalence of 1-52% [3,10,14], and radiographic studies indicate a prevalence of 14-33% (arterial CM) and 29-51% (venous CM) [19][20][21] (Tables 4, 5, and 6).…”
Section: Discussionmentioning
confidence: 99%
“…Letournel and Judet, among the first to use this nomenclature, questioned its clinical relevance, having encountered just one instance of this variant [7]. While anatomical studies indicate CM vessel prevalence of 33-83% [8][9][10][11][12][13], clinical studies report lower figures between 1-52% [3,10,14]. Only two studies in orthopedic pelvic surgery have addressed this topic, showing a prevalence of 1% and 38%.…”
Section: Introductionmentioning
confidence: 99%